Dismorfia institucional: um estudo de caso - Cunha, Tatiane Oliveira (Brasil, 2024)
This study aims to deepen the understanding of the role of institutional dysmorphia in shaping management strategies in public institutions, with a specific focus on the "BETA" Institute, a technical-scientific entity located in the State of Amazonas. The research adopts an exploratory-descriptive approach and employs a qualitative methodology, using a case study as a research strategy. Data were collected through direct observations and open interviews. The research results highlight significant challenges affecting the "BETA" Institute. Among these issues, the complexity of its organizational structure, the constant leadership turnover, the lack of continuity in institutional policies, intricate internal relationships, operational challenges, and the noticeable lack of a robust strategic planning are emphasized. The data analysis follows an inductive approach, starting from specific details and progressing to broader topics.